1994
DOI: 10.1128/jcm.32.3.790-792.1994
|View full text |Cite
|
Sign up to set email alerts
|

Bisulfite or sulfite inhibits growth of Helicobacter pylori

Abstract: Bisulfite or sulfite was found to be inhibitory to Helicobacter pyloni growth. A modified version of Brucella broth (BB), bisulfite-less BB (BLBB), supported rapid, robust, and consistent growth of H. pylori. We suggest that BLBB simply be called "Pylori broth" for distinction from Brucella broth. Helicobacter pylori, a gram-negative, spiral bacterium, has been implicated as the etiological agent for gastritis and as a major contributing factor in the development of peptic gastroduodenal ulcers (2, 5, 8, 9, 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 15 publications
3
20
0
Order By: Relevance
“…We reported the marked stimulation by hydrogen peroxide of the growth of H. pylori in Brucella broth medium. Hydrogen peroxide, which inactivated sodium bisulfite, promoted growth [5]. In the present study, we showed that the bactericidal effects of sodium bisulfite were stronger under acidic conditions than neutral conditions.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…We reported the marked stimulation by hydrogen peroxide of the growth of H. pylori in Brucella broth medium. Hydrogen peroxide, which inactivated sodium bisulfite, promoted growth [5]. In the present study, we showed that the bactericidal effects of sodium bisulfite were stronger under acidic conditions than neutral conditions.…”
Section: Discussionsupporting
confidence: 46%
“…This medium is composed of rich carbon and nitrogen sources, tryptone, peptamine, yeast extract, glucose, sodium chloride, and sodium bisulfite; the latter compound is added to decrease oxygen content. Hawrylik et al reported that sodium bisulfite inhibits the growth of H. pylori [5]. We observed previously that the addition of a low concentration of hydrogen peroxide eliminates this effect [6].…”
Section: Introductionmentioning
confidence: 58%
“…The effect of sodium sulfite added to the basic IHPA medium was a decrease in the number of colonies recovered, indicating that sodium sulfite was inhibitory to H. pylori growth. Our finding that sodium sulfite was inhibitory to H. pylori growth is comparable with the finding of other researchers (Hawrylik et al, 1994).…”
Section: Resultssupporting
confidence: 93%
“…In our laboratory, commercial Eugon agar (CEA) was extensively used to culture H. pylori. However, there have been reports that sodium sulfite (Hawrylik et al, 1994), one of the ingredients of CEA, was inhibitory to some H. pylori strains. The present study was aimed at modifying the original formulation of CEA with a view to develop a new H. pylori growth medium and to evaluate the new growth medium for the growth of other H. pylori isolates.…”
Section: Introductionmentioning
confidence: 99%
“…The strains were sub-cultured every 1-2 days. For preparation of culture supernatants, strains were swabbed from 24 h growth plates into 12 ml sulphite-free brucella broth containing 0.2% (w/v) b-cyclodextrin [14], and grown in a gas jar shaking in a microaerobic environment generated by a CampyPak for 2-3 days at 37°C…”
Section: Culturing Of Strains and Preparation Of Culture Supernatantsmentioning
confidence: 99%